Internalization of Islamic Religious Educational Values Through Role Playing Methods In The Learning of Aqidah Akhlak - Deny Hendrik; Zainal Effendi Berlian; Abdullah Idi (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to (1) find out the process of internalizing the values of Islamic religious education through the role-playing method in learning aqidah morals and (2) the implementation of the role-playing method in learning aqidah morals. The research results in internalizing the values of Islamic religious education through role-playing in learning aqidah morals to increase moral values, namely adab and manners, have been carried out effectively. Four steps are carried out in internalization: transformation, transaction, transinternalization, and evaluation. The method used is role-playing; its application starts from making lesson plans following the quality of learning, forming groups, and distributing worksheets.